2022
DOI: 10.1038/s41598-022-10826-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein and antigen profiles of third-stage larvae of Gnathostoma spinigerum assessed with next-generation sequencing transcriptomic information

Abstract: Gnathostomiasis is a food-borne zoonotic disease that can affect humans who eat improperly cooked meat containg infective third-stage larvae. Definitive diagnosis is through larval recovery. However, this is an invasive technique and is impractical if the larvae have encysted in inaccessible areas of the body. Antigen or antibody detection might be more interesting techniques for diagnosis. Proteomic could elucidate diagnostic markers and improve our understanding of parasite biology. However, proteomic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Lastly, proteomics analysis revealed the presence of G. spinigerum serpin and serine proteases in the patient's serum. Previous studies found that the excretory–secretory products of the third-stage G. spinigerum larvae include serpins, and it has been demonstrated that these serpins react with sera from gnathostomiasis patients ( Nuamtanong et al, 2019 ; Nogrado et al, 2022 ). By reducing host protease activity and modifying host immunity, parasite protease inhibitors thus act to make a safer environment for the host ( Ranasinghe and McManus, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, proteomics analysis revealed the presence of G. spinigerum serpin and serine proteases in the patient's serum. Previous studies found that the excretory–secretory products of the third-stage G. spinigerum larvae include serpins, and it has been demonstrated that these serpins react with sera from gnathostomiasis patients ( Nuamtanong et al, 2019 ; Nogrado et al, 2022 ). By reducing host protease activity and modifying host immunity, parasite protease inhibitors thus act to make a safer environment for the host ( Ranasinghe and McManus, 2017 ).…”
Section: Discussionmentioning
confidence: 99%